Emotional complexity of fan-controlled comments: Affective labor of fans of high-popularity Chinese stars - Wei, Yuruo (Frontiers in Communication, 2023)
In China, fan participation in media production is becoming more mainstream and diverse, and fan groups themselves are developing perceptible emotional attributes; thus, studies on affective labour involving fans are gradually increasing in number. Fan-controlled comments are a feature of fan culture that has received much attention due to their rapid growth and influence. This study uses sentiment analysis and keyword analysis to examine the main types of “emotions” felt by today’s fans of highly popular stars and classifies them into four categories: idols, fan communities, the self, and the outside world. Both positive and negative emotions coexist. The study found that fans engage in this kind of obligatory affective labour, creating second-hand exchanges for personal spiritual enrichment, and focusing more on building and expressing emotions. In addition, as affective labourers, they gain a sense of belonging to a fan community and form group symbols because of their shared emotions and concerns. Throughout the process of controlling comments, the time and energy of the fan groups are consumed, their emotions are controlled, and their behaviour is restrained; however, the immediate purpose they want to achieve is not achieved. What seems to be an active choice is a trap of alienated labour, bound, and controlled by forces.